Peculiarities of alginic acid hydration in the air and in hydrophobic organic environment - T. V. Krupskaya; N. V. Yelahina; L. P. Morozova; V. V. Turov (Хімія, фізика та технологія поверхні)
The effect of the medium on the parameters of water bound to the surface of alginic acid powder was studied by low-temperature 1H NMR spectroscopy. The aim of this work was to study the effect of hydrophobic environment on the binding of water with alginic acid and to compare the parameters of the interfacial layers of water in air, in chloroform and chloroform with the addition of hydrochloric acid. It is shown that when adsorbed on the surface (500 mg/g H2O), most of it is strongly bound. It is shown that for most dispersed systems, when replacing the air with chloroform, the interfacial energy of water increases from 11.8 to 15.2 kJ/mol, which is due to the capability of weakly polar organic molecules to diffuse on the surface of solid particles, thereby reducing the interaction energy with the adsorbed surface water clusters. It is concluded that chloroform molecules cannot diffuse on the surface of alginic acid particles and affect only the structure of water clusters localized in the outer adsorption layer. In the presence of hydrochloric acid on the surface of alginic acid, a system of water clusters is formed, most of which does not dissolve hydrochloric acid, and the radii of these clusters is 2 nm, which are likely to form in the gaps between the polymer chains of polysaccharide.